Konsep Intelegensi serta Perannya dalam Belajar dan Pembelajaran - Habsy, Bakhruddin All; Islamiyah, Fikrun Nadhofatul; Hutauruk, Andrea Briliana Christie; Sholihah, Mar’atus (Lembaga Yasin AlSys, 2024)
This research aims to find out the concept of intelligence and fun in studying and studying. Intelligence is closely related to the teaching and learning process, because the dominant factor in the learning process is an individual who is intelligent and able to think critically. So these factors dominate each other and influence the success of the learning process. A teaching and learning process that produces intelligent thinkers, both from intellectual, emotional and spiritual aspects, will be created if students have good intelligence so they can receive learning well too. Therefore, it is important to know that there is a role for intelligence in the teaching and learning process and achieving maximum learning outcomes.